Nitrogen and Phosphorus Rates’ Impact on Different Varieties of Alfalfa in Central Kansas - Mariana O. Mota; Luiz O. Pradella; Wallas M. da Silva; Romulo P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2023)
The United States is the largest producer of alfalfa (Medicago sativaL.) in the world, with a vast area grown under rainfed conditions. Under these conditions, and especially in a transition state such as Kansas, the alfalfa crop often suffers from water deficit stress. Environments under water-limited conditions promote a decrease in crop yield when inadequate water leads to an nitrogen deficiency and reduces crop biomass. This research aimed to investigate the production of different alfalfa varieties under different nitrogen and phosphorus rates in a rainfed environment. Three nitrogen application rates (0 lb/a; 200 lb/a; 400 lb/a) and three phosphorus application rates (0 lb/a; 100 lb/a; and 200 lb/a) provided nine combinations of application rates to four alfalfa varieties (54HVX41, Pioneer 54VR10, LOL 356HQRR, and DKA43-22RR). Five harvests were executed at 10% of flowering, and the whole plant biomass was collected to determine the dry matter in ton/a. Despite the statistically significant results of treatment interaction, there was no pattern in the average values of alfalfa production among different treatments and seasons. The collected weather data provided empirical evidence to support that precipitation and evapotranspiration (specifically under water stress) influenced alfalfa yield. The four genotypes used in this field study tended to be stable in their yield in response to fertilization.
Keywords: Medicago sativa L.; alfalfa yield; nitrogen; phosphorus